1998
DOI: 10.1111/j.1528-1157.1998.tb01311.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonconvulsive Status Epilepticus in the Critically Ill Elderly

Abstract: Summary:Purpose: To describe the electrographic and clinical features of nonconvulsive status epilepticus (NCSE) in the critically ill elderly and to identify potential predictors of outcome.Methods: We prospectively identified 25 episodes of altered mentation and NCSE in 24 critically ill elderly patients associated with generalized, focal, or bihemispheric epileptiform EEG patterns. Patients with anoxic encephalopathy were excluded.Results: Of 25 hospitalizations, 13 (52%) resulted in death, and 12 (48%) pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
173
0
7

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(187 citation statements)
references
References 19 publications
7
173
0
7
Order By: Relevance
“…The incidence of NCS in this model is 81%, the mean number of NCS/animal is 10.6 over a 2 hour observation period, and the mean duration of each episode is 60 sec (Hartings et al, 2003b). The occurrence and duration of NCS in brain injured patients are critical determinants of outcome and mortality (Jordan, 1995;Litt et al, 1998;Young et al, 1996). Although electric seizures and acute brain injury work synergistically to worsen outcome, the underlying pathomechanism is still unclear.…”
Section: Discussionmentioning
confidence: 92%
“…The incidence of NCS in this model is 81%, the mean number of NCS/animal is 10.6 over a 2 hour observation period, and the mean duration of each episode is 60 sec (Hartings et al, 2003b). The occurrence and duration of NCS in brain injured patients are critical determinants of outcome and mortality (Jordan, 1995;Litt et al, 1998;Young et al, 1996). Although electric seizures and acute brain injury work synergistically to worsen outcome, the underlying pathomechanism is still unclear.…”
Section: Discussionmentioning
confidence: 92%
“…Five patients had both clinical and subclinical seizures. In a series by Litt et al (12) of critically ill elderly patients, 24 patients were described to have nonconvulsive status epilepticus, but only two patients had a history of a known seizure disorder. In our series, three of the patients with subclinical seizures did not have a history of epilepsy, but the typical patient admitted to an EMU is not critically ill, representing a different patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, in some cases, excessive and overly aggressive treatment of seizures has also been reported to result in worsening of outcomes. 10 Several studies in animals have clearly shown the importance of treating non-convulsive seizures, which may be associated with increased metabolic, oxidative, and excitotoxic stress on brain at-risk, [13][14][15] and thus may result in irreversible neuronal injury. The management of NCSE is less clear in patients in whom NCSE presents as a manifestation of a serious underlying illness.…”
Section: Discussionmentioning
confidence: 99%